155k views
8 votes
Find the sum.

(
(-54x^(5)+35x^(3)-61)+(5x^(5)-69x^(3)-7)=

User Arunkumar
by
5.0k points

2 Answers

3 votes

Answer:
-49x^(5) - 34x^(3) - 68 or
49x^(5) + 34x^(3) + 68

Explanation:

Since both groups have the same variables and exponents, just align them and add.


-54x^(5)+5x^(5) = - 49x^(5)


35x^(3) - 69x^(3) = -34x^(3)

- 61 - 7 = - 68


-49x^(5) - 34x^(3) - 68

User Warkaz
by
4.5k points
4 votes

Answer:

125250

Explanation:

I just askeked and it gave me the answere

User Kost
by
4.7k points